Augmentation of Ca2+ signaling in astrocytic endfeet in the latent phase of temporal lobe epilepsy - Szokol, Karolina; Heuser, Kjell; Tang, Wannan; Jensen, Vidar; Enger, Rune; Bedner, Peter; Steinhäuser, Christian; Taubøll, Erik; Ottersen, Ole Petter; Nagelhus, Erlend A. (Frontiers in Cellular Neuroscience, 2015)
Astrocytic endfeet are specialized cell compartments whose important homeostatic roles depend on their enrichment of water and ion channels anchored by the dystrophin associated protein complex. This protein complex is known to disassemble in patients with mesial temporal lobe epilepsy and in the latent phase of experimental epilepsies. The mechanistic underpinning of this disassembly is an obvious target of future therapies, but remains unresolved. Here we show in a kainate model of temporal lobe epilepsy that astrocytic endfeet display an enhanced stimulation-evoked Ca2+ signal that outlast the Ca2+ signal in the cell bodies. While the amplitude of this Ca2+ signal is reduced following metabotropic glutamate receptor 5 (mGluR5) blockade, the duration is sustained. Based on previous studies it has been hypothesized that the molecular disassembly in astrocytic endfeet is caused by dystrophin cleavage mediated by Ca2+ dependent proteases. Using a newly developed genetically encoded Ca2+ sensor, the present study bolsters this hypothesis by demonstrating long-lasting, enhanced stimulation-evoked Ca2+ signals in astrocytic endfeet.